Microscopic assessment of cannabis sativa leaf extract on the histoarchitecture of the cerebellum in male wistar rats using transmission electron microscope (Nigerian Journal of Physiological Sciences, 2025)
Cannabis remains the most abused illicit substance in the world. The growing inclination towards decriminalization in several countries creates the need to clearly determine how consumption affects organs of the body, especially the brain. The aim of this research is to determine the effect of cannabis sativa on the histoarchitecture of the cerebellum and motor coordination in Wistar rats. Twenty-five male rats were divided into 5 groups (I-V): Group I received food and water, Group II received 10mg/kg and Group III received 20mg/kg of cannabis sativa aqueous leaf extract for 28 days. Groups IV & V received 10mg/kg and 20mg/kg of cannabis sativa for 28 days and were allowed for another 28 days recovery period. At the end animals were weighed and sacrificed by cervical dislocation. Result from Transmission Electron Microscope (TEM) sections of rat cerebellum in group I shows normal neurons and cellular architecture. Some degrees of cytoarchitectural and neuronal distortions were observed in animals exposed to cannabis. The extent of these distortion however were significantly reduced following a 28 day recovery period for both doses of cannabis administered. It can be deduced therefore that cannabis sativa exposure had significant adverse ultrastructural effects on the cerebellum of adult male Wistar rats.